Cancer Treatment-Induced Mucositis Pain: Strategies for Assessment and Management - Harris, Debra J (Dove Medical Press, 2006)
Mucositis pain is a major clinical problem associated with cancer treatment. Mucosal tissue injury is a dose-limiting side effect and also limits nutritional intake and oral function, resulting in weight loss and nutritional deficits for many patients. The pathophysiology of mucositis is thought to be a complex array of cytokine-mediated events, which begins with mucosal atrophy and eventually leads to the painful ulceration of the mucosa. This article reviews current research related to pain management for mucositis. Effective treatment for mucositis pain must be targeted at the various factors involved in the pain experience. Although a number of interventions aimed to prevent and treat mucositis have been studied, there is little evidence to recommend any one treatment modality. While current strategies for pain management rely on general treatment for acute pain, research developments are aimed at targeting the specific receptors and enzymes involved in mucositis. As these breakthroughs become available clinically, thorough assessment and timely directed interventions must be implemented in order to limit patient distress from mucositis. This article presents an assessment tool specific to mucositis pain, including physical, functional, and pain parameters.